Gender Diversity in the Boardroom and Earnings Quality: The Monitoring Role of Institutional Ownership - Budastra, Made Aditya; Isnalita, Isnalita (Accounting Analysis Journal, 2024)
Purpose : Earnings are a critical component of the income statement because most investors use them to make investment decisions in the company. Consequently, board of directors has a critical responsibility to present high-quality earnings reports and free from any elements of manipulation to ensure that investors are not misled when using them as a performance benchmark. The purpose of this study is to provide empirical evidence regarding the effect of board of directors’ gender diversity on earnings quality. Furthermore, this study also investigates the moderating role of institutional ownership on the effect of board of directors’ gender diversity on earnings quality. Method : The study uses a sample of 682 firm-year observations of manufacturing companies on IDX from 2015 to 2019. The data analysis technique used is Moderated Regression Analysis (MRA) with an Ordinary Least Square (OLS) approach. Findings : The study finds that the improvement in the quality of reported earnings is not determined by the level of gender diversity among company directors. Furthermore, this study also proves that the effectiveness of institutional ownership roles can help strengthen the gender diversity mechanism to improve the quality of reported earnings. This finding suggests that in developing countries such as Indonesia, the role of institutional ownership is effective in providing external monitoring of the firm’s board and reducing the board’s incentives to manipulate the firm’s earnings.  Novelty : The study is the first to examine the moderating role of institutional ownership in the board of directors’ gender diversity and earnings quality.